Pembentukan Peraturan Daerah yang Partisipatif - Hikam Mambaul; Husein Muslimin; Riski Febria Nurita (University of Merdeka Malang, 2020)
Community participation in the formation of participatory local regulations is an important thing in running a democracy, community participation here must be given a forum to accommodate inputs that can later be used as a strong reason for the formation of local regulations. Therefore, the community should be involved in the formation of local regulations in order to produce participatory properties. The research method used by the author is empirical, which is to describe the results of data obtained through interviews. The approach used is a sociological juridical approach that is to identify and conceptualize the law as a real and functional social institution in a real-life system regarding the Establishment of Participatory Regional Regulations. The results of this study were obtained by interviewing members of the DPRD, the malang city government, and the communities directly involved in the establishment of participatory local regulations. Community involvement is a mirror of the principle of openness in the establishment of legislation, although some of the public is still not aware of